The Utilization of Artificial Intelligence (AI) Based Digital Media to Realize Joyful Learning - Nurul Novitasari; A.M. Miftah Anshori; Siti Khoiriyah; Nur Lailatul Fitri (Universitas Al-Hikmah Indonesia, 2026)
This study aims to describe the use of Artificial Intelligence (AI) based digital media in creating joyful learning at TK Assurur Kedungjambe. The research subjects were 17 children from group A1. The digital media used were Wordwall and Animated Drawing, presented through an Interactive Flat Panel (IFP) that allowed children to interact directly with the media. The study employed a qualitative descriptive approach. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through technique triangulation and source triangulation. The results showed that the use of AI media was able to create an enjoyable learning atmosphere, with children actively engaged in motor, cognitive, and affective domains. Learning also became more contextual through the theme of family professions. The children appeared enthusiastic, focused, happy, and confident in expressing their ideas. The teacher acted as a facilitator, enabling a dialogic and participatory learning process. Thus, the integration of AI-based digital media has the potential to enhance motivation, creativity, and the quality of joyful learning for early childhood.